2019
DOI: 10.1002/jbio.201900177
|View full text |Cite
|
Sign up to set email alerts
|

Investigating pre‐analytical requirements for serum and plasma based infrared spectro‐diagnostic

Abstract: Infrared spectroscopy is a rapid, easy‐to‐operate, label‐free and therefore cost‐effective technique. Many studies performed on biofluids (eg, serum, plasma, urine, sputum, bile and cerebrospinal fluid) have demonstrated its promising application as a clinical diagnostic tool. Given all these characteristics, infrared spectroscopy appears to be an ideal candidate to be implemented into the clinics. However, before considering its translation, a clear effort is needed to standardise protocols for biofluid spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…To date, no analysis of these variables has been published. It has been shown that storage at low temperatures (−80°C) and storage in plastic tubes has no effect on generated spectra, whereas variations in sample drying can have an effect.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no analysis of these variables has been published. It has been shown that storage at low temperatures (−80°C) and storage in plastic tubes has no effect on generated spectra, whereas variations in sample drying can have an effect.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no publications or guide specifying the importance of the pre-analytical preparation of saliva used in VS. However, for blood sampling, it has been shown that storage at −80 °C and in plastic tubes has no effect on generated spectra, whereas variations in the drying and the storage of samples (fresh or frozen, avoid freeze-thaw cycles) can have an effect [ 49 ]. Therefore, standardization of saliva sample handling (collection, processing, and storage protocols) is crucial to ensure reproducibility and consistency in the results obtained as suggested by other reports [ 4 , 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This information would suggest that working with frozen samples can be beneficial to sample processing, as well as sample stability. Further studies by these authors have also illustrated that long term storage of samples does not have significant impact on spectral output [54,60].…”
Section: Pre-clinical Considerationsmentioning
confidence: 99%
“…Due to the complex composition of blood serum, drying patterns are prominent within dried serum spots, with the coffee ring effect commonly observed as a confounding factor in transmission and transflection FTIR spectroscopy studies [15,16]. The large sampling area employed in the ATR modality of FTIR spectroscopy, determined by the IRE surface area, helps to overcome spectral variance that can arise from these patterns due macro-measurements of the entire serum spot; however, controlled drying conditions have been shown to improve spectral reproducibility [54,60,65]. The drying environment is crucial to serum drop homogeneity, with humidity, temperature and air flow having significant impact on macromolecule spread in the serum drop, as well as crack features, which are known to cause spectra distortions in all modalities of FTIR spectroscopy [65].…”
Section: Pre-clinical Considerationsmentioning
confidence: 99%